2010
DOI: 10.1073/pnas.0912877107
|View full text |Cite
|
Sign up to set email alerts
|

A molecular mechanism underlying the neural-specific defect in torsinA mutant mice

Abstract: A striking but poorly understood feature of many diseases is the unique involvement of neural tissue. One example is the CNSspecific disorder DYT1 dystonia, caused by a 3-bp deletion ("ΔE") in the widely expressed gene TOR1A. Disease mutant knockin mice (Tor1a ΔE/ΔE ) exhibit disrupted nuclear membranes selectively in neurons, mimicking the tissue specificity of the human disease and providing a model system in which to dissect the mechanisms underlying neural selectivity. Our in vivo studies demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
206
3
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(230 citation statements)
references
References 20 publications
16
206
3
1
Order By: Relevance
“…Constitutive knockout of LAP1 in mice causes perinatal lethality; however, a very recent study reported that the conditional deletion of LAP1 from mouse striated muscle leads to muscular dystrophy whereas LAP1 deletion from hepatocytes does not affect liver function [13,26]. This model supports the notion that LAP1B has a specific role in striated muscle and represents a functional validation of the effect of LAP1B deficiency in human striated muscle.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Constitutive knockout of LAP1 in mice causes perinatal lethality; however, a very recent study reported that the conditional deletion of LAP1 from mouse striated muscle leads to muscular dystrophy whereas LAP1 deletion from hepatocytes does not affect liver function [13,26]. This model supports the notion that LAP1B has a specific role in striated muscle and represents a functional validation of the effect of LAP1B deficiency in human striated muscle.…”
Section: Discussionsupporting
confidence: 59%
“…Although knockdown of LAP1 or LULL1 does not seem to affect expression or localization of torsinA, mice lacking LAP1 exhibit perinatal lethality and LAP1 deficiency causes nuclear membrane abnormalities similar to those observed in torsinA-null cells [13,27]. On the other hand, overexpression of LAP1 and LULL1 recruits torsinA to the nuclear envelope [11,28].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A conditional deletion of TorA from the CNS in mice accurately replicates the symptoms of primary dystonia (14). In addition, LAP1-deficient mice display early perinatal lethality (15), again corroborating the physiological significance of regulation and dysregulation of Torsin activity.…”
mentioning
confidence: 64%
“…Although studied extensively, the function of LAP1 remains unclear. A recent report utilizing torsinA mutant mice showed that LAP1 and torsinA act in the same biological pathway required for normal nuclear membrane morphology in both neuronal and non-neuronal cells (44). The C-terminal lumenal domain of LAP1B is highly conserved, but its function is unknown; the N-terminal nucleoplasmic domain and the transmembrane span of LAP1B are necessary and sufficient for the nuclear localization of the molecule (45).…”
Section: Discussionmentioning
confidence: 99%